Perancangan Ulang Tata Letak Fasilitas Menggunakan Metode Systematic Layout Planning (SLP) Dengan Alogaritma Blocplan Di UD Wijaya Samawa - adiasa, iksan; Mashabai, Ismi (Fakultas Teknik Universitas Tulang Bawang, 2024)
Fish is the product of various types of natural resources and is widely consumed by most people. Based on data obtained from the Office of Maritime Affairs and Fisheries of West Nusa Tenggara, Sumbawa is ranked second in West Nusa Tenggara as an area with high potential in the world of fisheries and it is very likely that many people will be involved in the world of fisheries. One of the fish supply companies located in the city of Sumbawa is UD Wijaya Samawa. This company is engaged in catching, processing and selling fish. However, in the fish packaging production process, there are problems with inefficient placement of facilities and layout resulting in waste of both time and place, thus disrupting the ongoing production process. One method that can be used to streamline production process facilities is the Systematic Layout Planning (SLP) method. As for determining alternative layout proposals, namely by using the BLOCPLAN Algorithm based on the ARC that has been made. The results of this study are alternative layout proposals that can minimize the distance from the previous 54 meters to 35.53 meters so that the distance can be reduced by 18.47 meters. Keywords: Activity Relationship Chart, BLOCPLAN, Layout, Systematic Layout Planning